2014
DOI: 10.15407/spqeo17.04.398
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Schottky barrier height in diodes based on Au-TiB2-n-SiC 6H from the current-voltage and capacitance-voltage characteristics

Abstract: Abstract. We present the results of investigation of the barrier height and ideality factor in Schottky barrier diodes based on Au-TiB 2 -n-SiC 6H relying on measuring the current-voltage and capacitance-voltage characteristics. Improving the accuracy of the methods that take into account the effect of the series resistance in calculating the ideality factor and barrier height has been shown with the Cheung method and direct approximation one. It has been ascertained that an inconsistency between real currentv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…It is pertinent to note that there are variations in actual values of barrier height, ideality factor, and series resistance from one model to another, which might be due to differences in boundaries of I-V characteristics used in each model. Similar observations were made by Kudryk et al 55 It is observed from the extracted I-V parameters that in the temperature range of 300-423 K, the barrier height and ideality factor are in the range of 0.82 eV-1.16 eV and 0.68-0.41 for the TiN-SiC-Au structure (from standard thermionic emission), respectively. The values of the barrier height for the Au/TiN-SiC-Au structure are in the range of 0.78 eV (at 300 K) to 0.93 eV (at 393 K) and 0.77 eV (at 423 K), while the ideality factor for this structure is in the range of 0.73-0.35 (300-423 K).…”
Section: Resultssupporting
confidence: 88%
“…It is pertinent to note that there are variations in actual values of barrier height, ideality factor, and series resistance from one model to another, which might be due to differences in boundaries of I-V characteristics used in each model. Similar observations were made by Kudryk et al 55 It is observed from the extracted I-V parameters that in the temperature range of 300-423 K, the barrier height and ideality factor are in the range of 0.82 eV-1.16 eV and 0.68-0.41 for the TiN-SiC-Au structure (from standard thermionic emission), respectively. The values of the barrier height for the Au/TiN-SiC-Au structure are in the range of 0.78 eV (at 300 K) to 0.93 eV (at 393 K) and 0.77 eV (at 423 K), while the ideality factor for this structure is in the range of 0.73-0.35 (300-423 K).…”
Section: Resultssupporting
confidence: 88%
“…Even though the condition of V ≥ 3kT/q is satisfied, the I-V curve obtained from the linear region is showing a bowing effect making it difficult to choose a suitable voltage to interpret the Schottky parameters. Several researchers [29,[31][32][33] also addressed the same behavior in their papers. It is well-known that the electrical characteristic of a Schottky diode is strongly influenced by ideality factor, series resistance, and leakage current [34,35].…”
Section: Extraction Of Schottky Parametersmentioning
confidence: 95%
“…Important parameters of the Schottky junction, which are Schottky barrier height (ф B ), ideality factor (n), and series resistance (R s ), are extracted from the forward I-V characteristic at various temperatures. The calculation of the parameters is derived from the Schottky diode equation which follows the thermionic emission model shown in Equation 2 [28][29][30].…”
Section: Extraction Of Schottky Parametersmentioning
confidence: 99%
See 1 more Smart Citation